PENGARUH KEPEMILIKAN MANAJERIAL, DEWAN KOMISARIS INDEPENDEN, DAN KOMITE AUDIT TERHADAP NILAI PERUSAHAAN PADA SEKTOR PROPERTI DAN REAL ESTATE DI BEI - Fauziah, Dewi Syifa; Suherman, Suherman; Ahmad, Gatot Nazir (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2024)
This study aims to determine the influence of managerial ownership (MO), independent board of commissioners (IC), and audit committee (AC) on firm value proxied by Price to Book Value (PBV) and Tobin's Q, using both proxy models. The research sample was selected using purposive sampling, covering 88 property and real estate companies listed on the Indonesia Stock Exchange (IDX) for the period 2020 – 2023. This study uses secondary data in the form of annual reports. The analytical technique used is panel data regression with the Random Effect Model approach using Eviews 12 software. The results show that MO has a positive but not significant effect on firm value in both PBV and Tobin's Q models. IC has a positive but not significant effect on firm value in both PBV and Tobin's Q models. AC has a negative and not significant effect on firm value in both PBV and Tobin's Q models